Residue Oil Desulfurization Using Oxidation and Extraction Method - Rizky Tetrisyanda; Annas Wiguno; Rizqy Romadhona Ginting; M. Chadiq Dzikrillah; Gede Wibawa (Universitas Gadjah Mada, 2018)
This study successfully improved the performance of oxidative desulfurization method to reduce sulfur content from residue oil (condensate) with modifications of oxidation and extraction steps which was repeated for several stages. Residue oil used in this study contain 386.2 ppm of initial sulfur content. In oxidation process, H2O2 as oxidizer and acid as catalyst were used within temperature range of 30–60 °C and time interval from 30 to 120 min. In extraction process, various alcohol solvents (methanol, ethanol, and propanol) were used with the temperature of 30 °C in 30 min for every residue oil ratio to solvent (v/v). The best reducing sulfur result achieved was 35.9 ppm or 90.7% desulfurization. This result was achieved after 4 recursively extractions using ethanol as solvent. This study successfully reduced sulfur content in residue oil to meet the international standard (< 50 ppm).